1226 Parental experience interviews: part of a direct NICU to PCCU transfer service improvement project. (17th August 2022) - Patel, Shil; Silvestre, Catarina; Kigozi, Phoebe
Abstract : Aims: As part of a service improvement project, we aimed to ascertain parental experiences when transitioning between the Neonatal Intensive Care Unit (NICU) and the Paediatric Critical Care Unit (PCCU). Methods: In this study, parents of infants hospitalised at the Nottingham University Hospitals (NUH) tertiary NICU and directly transferred to PCCU were enrolled. Parents were invited for an interview by a family care team administrator who also plays a key role in the NICU parental support group. Parents who agreed to an interview were then contacted at their convenience and verbally consented by Dr Shil Patel. The interviews were performed using a semi-structured format to establish the background summary of their case, information received about the transfer and opinions on some suggested interventions. Open questions were used to elicit their personal experiences. The interviews were not recorded but indirect quotations were recorded with key themes noted. Results: Four parent interviews were undertaken, representing 10% of NICU to PCCU transfers at NUH over the last 10 years. Two were ex-preterm current PCCU patients, with one awaiting a tracheostomy and one weaning tracheostomy ventilation. Two were children who had surgical airways and were two years post discharge. 6 key themes emerged including clarity/amount of information received, differences in care approaches, expectations around parental involvement and outcomes, pre-transfer tours, available support for parents and finally the perceptions around transfer. Figure 1 . Key quotes outlined in table 1 . Parents wanted more information, seeking information elsewhere, and felt that it was 'empowering when more information is given'. They noticed the 'culture' difference between the two units, even minor aspects like the number of bedside toys. They also struggled to understand why the approach to management was so different 'when the child is the same'. The expectation of the plan prior to transfer was also a key talking point, with all parents having the expectation of going to PCCU to wean respiratory support and go home. Perception of the transfer was also key as many felt the day of transfer was rushed and due to 'bed pressure'. The parents who received tours before transfer greatly appreciated them. One stating that they still remember the doctor and nurse who conducted them. Parents overall felt more supported on NICU. They found it difficult to relate to other parents on PCCU and got much of their support outside of the units, through social media and groups. Conclusion: In a limited number of parent interviews, we observed that families struggle with transition periods, whether that is admission, step downs or transfers. Children transferred directly from NICU to PCCU make up a very low number of patients. However, they occupy disproportionate resources. They frequently go on to require further support in the community. The parents need to be supported to look after their children who have complex needs in hospital and perhaps beyond. These results are informing our local improvement plan for the transition of care pathways between NICU and PCCU; and should be considered by other units with similar patients.